2023
DOI: 10.17135/jdhs.2023.23.2.69
|View full text |Cite
|
Sign up to set email alerts
|

The Review of Interventions to Improve the Swallowing Function in the Elderly

Abstract: Background: Swallowing function deterioration is a common problem experienced by older adults worldwide. Many studies have been conducted to improve swallowing function in older adults; however, due to differences in intervention methods and study designs, it is difficult to draw a common conclusion. This study aimed to analyze trends and intervention methods in studies of swallowing function intervention for older adults conducted from 2010 to 2022, to establish a systematic approach for developing interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Dysphagia is a major cause of aspiration pneumonia 7,8) , which is a leading cause of death among older adults. Dysphagia has been reported in 15∼22% of communitydwelling older adults in the United States 9) . The Korean Dysphagia Society reported that 30∼40% of older adults aged ≥65 years in Korea are diagnosed with dysphagia.…”
Section: Introductionmentioning
confidence: 99%
“…Dysphagia is a major cause of aspiration pneumonia 7,8) , which is a leading cause of death among older adults. Dysphagia has been reported in 15∼22% of communitydwelling older adults in the United States 9) . The Korean Dysphagia Society reported that 30∼40% of older adults aged ≥65 years in Korea are diagnosed with dysphagia.…”
Section: Introductionmentioning
confidence: 99%